Immunization technologies: Time to consider new preventative solutions for respiratory syncytial virus infections - Catherine Weil-Olivier; David Salisbury; José Antonio Navarro-Alonso; Chryssoula Tzialla; Yan Zhang; Susanna Esposito; Fabio Midulla; Tobias Tenenbaum (Taylor & Francis Group, 2023)
New technologies for the prevention of infectious diseases are emerging to address unmet medical needs, in particular, the use of long-acting monoclonal antibodies (mAb) to prevent Respiratory Syncytial Virus (RSV) lower respiratory tract disease in infants during their first RSV season. The lack of precedent for mAbs for broad population protection creates challenges in the assessment of upcoming prophylactic long-acting mAbs for RSV, with associated consequences in legislative and registration categorization, as well as in recommendation, funding, and implementation pathways. We suggest that the legislative and regulatory categorization of preventative solutions should be decided by the effect of the product in terms of its impact on the population and health-care systems rather than by the technology used or its mechanism of action. Immunization can be passive and active, both having the same objective of prevention of infectious diseases. Long-acting prophylactic mAbs work as passive immunization, as such, their recommendations for use should fall under the remit of National Immunization Technical Advisory Groups or other relevant recommending bodies for inclusion into National Immunization Programs. Current regulations, policy, and legislative frameworks need to evolve to embrace such innovative preventative technologies and acknowledge them as one of key immunization and public health tools.